2014
DOI: 10.1186/1471-2261-14-81
|View full text |Cite
|
Sign up to set email alerts
|

Congenital coronary anomalies detected by coronary computed tomography compared to invasive coronary angiography

Abstract: BackgroundAs coronary computed tomography angiography (CCTA) has emerged as a non-invasive alternative for evaluation of coronary anatomy with a lower referral threshold than invasive coronary angiography (ICA), the prevalence of coronary anomalies in CCTA may more closely reflect the true prevalence in the general population. Morphological features of coronary anomalies can be evaluated more precisely by CCTA than by ICA, which might lead to a higher identification of congenital coronary anomalies in CCTA com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
57
1
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(76 citation statements)
references
References 35 publications
0
57
1
5
Order By: Relevance
“…Anomalies of coronary termination. (4,5) We did not encounter any case of anomaly of coronary artery termination.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Anomalies of coronary termination. (4,5) We did not encounter any case of anomaly of coronary artery termination.…”
Section: Discussionmentioning
confidence: 91%
“…(4) However with the increasing use of MDCT angiography, the prevalence of coronary artery anomalies have increased. In our study the prevalence was about 6.4 %.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, its widespread use is limited due the dose of ionizing radiation and the use of contrast agents, in particular taking into account that most patients are young. A recent study showed that the prevalence of CAAs is substantially higher with CT than coronary angiography, suggesting a possible underestimation of CAAs based on invasive angiography [53] . CMR is capable of visualizing the origin of the coronary arteries non-invasively, without use of ionizing radiation and contrast agents.…”
Section: Imagingmentioning
confidence: 99%
“…Coronary CT offers the best performance in terms of spatial resolution, acquisition time, and image contrast. Furthermore, in a study comparing coronary CT and coronary angiography, it was demonstrated that the prevalence of coronary anomalies detected was substantially higher by coronary CT [3]. …”
Section: Discussionmentioning
confidence: 99%